Changes in Production Structure and Natural Gas Consumption in Iran’s Provinces: Spatial Econometric Approach - Fatemeh Oveysi Kahkha; Ramezan Hosseinzadeh (Environmental Energy and Economic Research)
change in production structure of an economy is one of the factors affecting economic variables such as energy consumption in different economic activities. Therefore, the purpose of this study is to investigate the direct and spillover effects of structural changes in production on natural gas consumption in different provinces of Iran during 2007-2018 using spatial econometrics approach. In this study, two indices including industry share in total output and the structural change index (NAV) were used to measure structural changes in the production of the economy. The results indicate that the direct effects of all variables except natural gas price are positive and significant. The direct effect of natural gas price (LGP) on the consumption of this energy is negative and significant. The direct effect of GDP, industrialization, production structure change and urbanization were positive and significant. Spillover effect of the industrialization and change in production structure were positive and significant on natural gas consumption